Associação das variantes da região carboxiterminal do gene cagA de Helicobacter pylori com o desenvolvimento de distúrbios gastroduodenais em Belém-Pará - SILVA, Adenielson Vilar e (Universidade Federal do Pará, 2017)
Helicobacter pylori CagA cytotoxin, encoded by the cagA gene, has been associated with increased inflammatory response in gastric tissue and the change in control of cell growth and proliferation. Activation of this cytotoxin occurs by phosphorylation in specific tyrosine residues within an amino acid sequence termed motif EPIYA, four types of motifs are described in the literature (EPIYA-A,-B-C and D). However, the site EPIYA-C is the most common site of phosphorylation of CagA protein of the bacterial strains isolated in Western countries, may still be found in repetitions. This study aimed to determine the types of motifs EPIYA of CagA present in patients with gastritis and gastric cancer and its association with these diseases. Were collected samples from gastric biopsies of 384 patients infected with H. pylori, of this 194 presented chronic gastritis and 190 had gastric cancer. The gastric biopsy was used for bacterial DNA extraction and analysis of the cagA gene by PCR. The prevalence of gastric cancer occurs in males, mean age 58 years. The cagA gene was more prevalent in patients with gastric cancer, showing association with a higher degree of inflammation, neutrophil activity and development of intestinal metaplasia (OR = 4,31, IC 95% = 2,71-6,87, p <10-3; OR = 3,57, IC 95% = 2,18 – 5,84, p <10-3; OR = 11,11, IC 95% = 5,48 – 22,30, p <10-3; OR = 3,65, IC 95% = 1,50-8,88, p=0,004, respectively). The number of repetitions EPIYA-C site was significantly associated with increased risk of gastric cancer (OR = 2,99, IC 95% = 1,53-5,82, p <10-3). The higher number of motifs EPIYA-C was also associated with intestinal metaplasia (p = 0,02). In this study the infection by strains of H. pylori carriers cagA gene with more than one motif EPIYA-C shown to be associated with the development of intestinal metaplasia and gastric cancer, but without an association to neutrophil activity and degree of inflammation.